2006
DOI: 10.1186/1471-2164-7-160
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of Spodoptera frugiperda hemocytes and fat body using cDNA microarray reveals polydnavirus-associated variations in lepidopteran host genes transcript levels

Abstract: BackgroundGenomic approaches provide unique opportunities to study interactions of insects with their pathogens. We developed a cDNA microarray to analyze the gene transcription profile of the lepidopteran pest Spodoptera frugiperda in response to injection of the polydnavirus HdIV associated with the ichneumonid wasp Hyposoter didymator. Polydnaviruses are associated with parasitic ichneumonoid wasps and are required for their development within the lepidopteran host, in which they act as potent immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 116 publications
2
30
0
3
Order By: Relevance
“…Microarray experiments showed that two PGRPs of Drosophila were significantly upregulated after parasitoid attack [49]. Hyposoter didymator polydnavirus infection can down-regulate a Spodoptera frugiperda gene with high similarity with the Manduca sexta immulectin-2 [50]. Especially, it was reported that the gene lectin - 24A was massively up-regulated in parasitized Drosophila larvae after parasitization at the time when the capsule was formed [51].…”
Section: Resultsmentioning
confidence: 99%
“…Microarray experiments showed that two PGRPs of Drosophila were significantly upregulated after parasitoid attack [49]. Hyposoter didymator polydnavirus infection can down-regulate a Spodoptera frugiperda gene with high similarity with the Manduca sexta immulectin-2 [50]. Especially, it was reported that the gene lectin - 24A was massively up-regulated in parasitized Drosophila larvae after parasitization at the time when the capsule was formed [51].…”
Section: Resultsmentioning
confidence: 99%
“…The Vinnexins initially were hypothesized to disrupt hemocytic encapsulation, the primary anti-parasitoid immune response of caterpillars, presumably by inhibiting gap junctional intercellular communication [78,79]. Like many IV genes, vinnexin transcripts are broadly detected in host caterpillar tissues [31,97]. However, an antibody against the C. sonorensis IV (CsIV) VinnexinQ2 (Cs-VnxQ2) only identified the protein in CsIV-infected hemocytes of the caterpillar Heliothis virescens, where the protein localized to cellular membranes [31].…”
Section: Vinnexins Of Polydnavirusesmentioning
confidence: 99%
“…Transcriptomic analyses of these particular host-parasitoid interactions have so far focused on host genes (26,27) or on specific virulence genes or multigenic families and have rarely given a global vision of PDV transcription during these interactions (3,5,28). Recently, an extensive BV transcriptome profile was reported, which concerned Microplitis demolitor BV (MdBV) expression in Pseudoplusia includens, where the spatial and temporal expressions of most predicted open reading frames (ORFs) of this BV were analyzed by reverse transcription-PCR (RT-PCR) (29).…”
Section: Importancementioning
confidence: 99%